Critical Literacy in Arabic Language Learning: (Implementation of GBA SFL in Improving Critical Reading Ability) - Hasanah, Mamluatul; Mubaligh, Ahmad; Sari, Risna Rianti; Syarofah, Alfiatus; Amrullah, Hasyim; Barry, Muhammad Yasin Fatchul (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This research aimed to create a prototype of the construction of learning to read Arabic with a critical literacy approach based on the SFL GBA and its implementation in learning reading skills. The systemic functional linguistics’ genre-based approach (SFL-GBA) was used to foster a critical attitude towards reading in the scope of Arabic Language Education students’ reading skills. The method used was action research, with the hope that PBA students of UIN Maulana Malik Ibrahim Malang could have critical reading competencies. The results of this study demonstrated a prototype of the construction of learning Arabic reading skills with a critical literacy approach based on the SFL GBA and the guidance of the prototype implementation in the Arabic reading skills class. After this action, students could find out the types of text, the structure, and linguistic features of the text, to later be criticized according to the data they got.